2012
DOI: 10.1039/c1jm14193g
|View full text |Cite
|
Sign up to set email alerts
|

Formation of gold nanoparticles in polymeric nanowires by low-temperature thermolysis of gold mesitylene

Abstract: The formation of polymer nanowires containing metal nanoparticle chains by low-temperature thermolyses of metal precursors has remained challenging. We report the block copolymer-assisted generation of locally regular chains of quasi-spherical gold nanoparticles with narrow particle diameter distribution by mild thermolysis of the non-polar gold precursor gold mesitylene inside the cylindrical nanopores of self-ordered anodic aluminium oxide (AAO). The block copolymer separates the gold mesitylene as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Therefore, improving the photostability of UV screening materials is still a challenge. Literatures and our experiments have shown that the un‐assembled Au(I)‐thiolates are easy to transform to gold clusters or gold nanoparticles by chemical reduction, [37–40] thermolysis [41] or photolysis [42] . Here, we studied whether the assembled Au(I)‐thiolate nanosheets can have comparable or superior photostability to the commercial organic UV absorbents.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, improving the photostability of UV screening materials is still a challenge. Literatures and our experiments have shown that the un‐assembled Au(I)‐thiolates are easy to transform to gold clusters or gold nanoparticles by chemical reduction, [37–40] thermolysis [41] or photolysis [42] . Here, we studied whether the assembled Au(I)‐thiolate nanosheets can have comparable or superior photostability to the commercial organic UV absorbents.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, it is necessary to synthesize nanoparticles as monodisperse as possible. To this end, thermolitic methods consist of the application of a thermal stimulus on the coated nanoparticles with the aim of producing nucleation processes that lead to the controlled growth of the metallic core [44][45][46]. In general, the procedure involves the thermal treatment of the nanoparticles at a given temperature for a period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, the extremely high temperatures of the heat treatment or the presence of the metal salt in the hot solution can lead to the aggregation or decomposition of the metallic core and the organic ligands, thus losing the homogeneity of the hybrid system. As a result, a more environmentally friendly approach to synthesis and control of metallic NPs becomes necessary. …”
Section: Introductionmentioning
confidence: 99%